Comparative analysis of informed consent for spine surgery in patients in Ethiopia and Poland and the importance of verbal contact with patients based on the medical mission "Polish Medical Team Helping Hand" - Siedlecki, Zygmunt; Sahlu, Abat; Sileshy, Adu; Mendere, Surafel Mekonnen; Dilnesaw, Amanuel Firew; Bizuneh, Yemisirach; Grzyb, Sebastian; Tegene, Bizuayehu Mengesha; Tirsit, Abenezer; Śniegocki, Maciej (Journal of Education, Health and Sport, 2022)
The authors present a comparative analysis of the issue of legal consents for surgical procedures between Ethiopia and Poland. The analysis is based on the procedures performed as part of the Polish medical mission "Polish Medical Team Helping Hand". As part of this project, the authors performed ten surgical procedures for percutaneous spine stabilization in soldiers injured during the war with gunshots of the spine and after falling from a height. All soldiers signed informed written consent to the procedure. However, the authors noticed a significant role of additional oral/ verbal (not written) information in discussing the details of the procedure, which in Polish hospitals must be in writing for formal and legal reasons. The authors conclude that while the written consent for surgical treatment is key and necessary both in Poland and in Ethiopia, in the case of medical procedures performed in Ethiopia, oral communication between the doctor and patients and oral explanations are more binding even regardless of the language barrier.